Identification of long non-coding RNA-microRNA-mRNA regulatory modules and their potential roles in drought stress response in wheat (Triticum aestivum L.) - Li, Ning; Liu, Tongtong; Guo, Feng; Yang, Jinwen; Shi, Yugang; Wang, Shuguang; Sun, Daizhen (Frontiers in Plant Science, 2022)
Drought is one of the most severe abiotic stresses that influences wheat production across the globe. Understanding the molecular regulatory network of wheat in response to drought is of great importance in molecular breeding. Noncoding RNAs influence plant development and resistance to abiotic stresses by regulating gene expression. In this study, whole-transcriptome sequencing was performed on the seedlings of two wheat varieties with contrasting levels of drought tolerance under drought and control conditions to identify long noncoding RNAs (lncRNAs), micro RNAs (miRNAs), and mRNAs related to drought stress and explore the potential lncRNA-miRNA-mRNA regulatory modules in controlling wheat drought stress response. A total of 1515 differentially expressed lncRNAs (DELs), 209 differentially expressed miRNAs (DEMs), and 20462 differentially expressed genes (DEGs) were identified. Of the 20462 DEGs, 1025 were identified as potential wheat drought resistance-related DEGs. Based on the regulatory relationship and expression patterns of DELs, DEMs, and DEGs, 10 DEL-DEM-DEG regulatory modules related to wheat drought stress response were screened, and preliminary expression verification of two important candidate modules was performed. Our results revealed the possible roles of lncRNA-miRNA-mRNA modules in regulatory networks related to drought tolerance and provided useful information as valuable genomic resources in molecular breeding of wheat.